Emerging mechanisms and implications of cGAS-STING signaling in cancer immunotherapy strategies - Jiawen Zhang; Sihui Yu; Qiao Peng; Ping Wang; Lan Fang (Cancer Biology & Medicine, 2024)
The intricate interplay between the human immune system and cancer development underscores the central role of immunotherapy in cancer treatment. Within this landscape, the innate immune system, a critical sentinel protecting against tumor incursion, is a key player. The cyclic GMP-AMP synthase (cGAS) and stimulator of interferon genes (STING) pathway has been found to be a linchpin of innate immunity: activation of this signaling pathway orchestrates the production of type I interferon (IFN-α/β), thus fostering the maturation, differentiation, and mobilization of immune effectors in the tumor microenvironment. Furthermore, STING activation facilitates the release and presentation of tumor antigens, and therefore is an attractive target for cancer immunotherapy. Current strategies to activate the STING pathway, including use of pharmacological agonists, have made substantial advancements, particularly when combined with immune checkpoint inhibitors. These approaches have shown promise in preclinical and clinical settings, by enhancing patient survival rates. This review describes the evolving understanding of the cGAS-STING pathway’s involvement in tumor biology and therapy. Moreover, this review explores classical and non-classical STING agonists, providing insights into their mechanisms of action and potential for optimizing immunotherapy strategies. Despite challenges and complexities, the cGAS-STING pathway, a promising avenue for enhancing cancer treatment efficacy, has the potential to revolutionize patient outcomes.